What would Susie say? : bullshit wisdom about love, life, and comedy - Essman, Susie, 1955- (Simon & Schuster, 2009)
Susie Essman sheds the crasser layers to reveal how she went from an anxiety-ridden, struggling stand-up comic to being one of the funniest women on television, while also providing sidesplittingly funny wisdom on a range of topics that she's highly unqualified to expound upon, including men, sports, hypochondria, and stepparenthood.